Psychological Aspects of the Role of Product Advertising Against Consumer Purchase Interest: Study of Gain Mass Milk Advertising at Gymnastic - Alfatih, Andy; Septian, Muhammad Rio (Open Access Indonesia Journal of Social Sciences, 2018)
Abstract Introduction.The main purpose of advertising certain products or services is to attract customer attention and analyze the impact of advertising on customer behavior. Various studies show that there are significant links between cognitive and psychological aspects. The cognitive effect of an advertisement begins with the influence of the visual aspects of the advertisement. This research was aimed to explore the role of product advertising on consumer buying interest by studying aspects of psychology. Methods. The study design was observational analytic study that seek to see the relationship between exposure to milk mass forming muscle mass and consumer buying interest. The exploration dimensions for advertising exposure are ad frequency, ad duration and ad intensity using questionnaire. Total samples in this study were 60 people, age ranges from 18-35 years and male sex. Results. This study found as many as 70% of respondents understood the message delivered by the milk advertisement. As many as 56.7% of respondents expressed an interest in buying these muscle-building milk products. Around 58% of respondents stated their willingness to promote the product to others. Conclusion. This research shows the role of advertising in shaping consumer behavior and buying interest. The more attractive and the more often the ad is displayed it will trigger aspects of attractiveness and confidence in the product. Along with the need, further reinforce the behavior to buy products.